If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying -2 + -2 = -6 + x Combine like terms: -2 + -2 = -4 -4 = -6 + x Solving -4 = -6 + x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-1x' to each side of the equation. -4 + -1x = -6 + x + -1x Combine like terms: x + -1x = 0 -4 + -1x = -6 + 0 -4 + -1x = -6 Add '4' to each side of the equation. -4 + 4 + -1x = -6 + 4 Combine like terms: -4 + 4 = 0 0 + -1x = -6 + 4 -1x = -6 + 4 Combine like terms: -6 + 4 = -2 -1x = -2 Divide each side by '-1'. x = 2 Simplifying x = 2
| 18x+6-21-2x= | | F(X)=-6X-3+X(3X-7) | | (2w-3y)*(2w+7)= | | y=15/y+2y/10 | | (s^2-10s+16)/(s+2) | | 5b-6-12b-8= | | K=(s^2-10s+16)/(s+2) | | 0,5^5-5x/2x-31 | | 50-40x=50 | | 41-x=3(5x+3) | | F(X)=3X-4+X(9X-7) | | 3h^2-60=24h | | 9y+5x=10 | | y=11x^2+5x+13 | | 3h+9=4h-3 | | c+3=15-3c | | (x-80)/X=0.2 | | 4(2x-4)=8x+56 | | 4(2x-4)=8x+36 | | 4(2x-4)=8x+20 | | 4(2x-4)=8x+19 | | 4(2x-4)=8x+18 | | 4(2x-4)=8x+17 | | 4(2x-4)=8x+15 | | 4(2x-4)=8x+14 | | 4(2x-4)=8x+12 | | 3cosx+5sinx-5=0 | | 4(2x-4)=8x+0 | | 4(2x-4)=8x+9 | | 4(2x-4)=8x+7 | | 4(2x-4)=8x+6 | | 4(2x-4)=8x+5 |